Tim Prodi Kalk PIP Semarang Membantu FGD AMY dalam Rangka Pengabdian Kepada Masyarakat - Winarno Winarno (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
Semarang Merchant Marine Polytechnic (PIP) assigned the study program of Sea Transportation and Port Management (KALK) to assist in Focus Group Discussion (FGD) at the Maritime Academy of Yogyakarta (AMY) in the framework of implementing community service. This assignment was based on a letter of request from the Director of AMY to the Director of PIP Semarang to send expert speakers from KALK to help provide the guidance and experience on the FGD of Commercial Shipping (KPN) Study Program in AMY. AMY is supposed to carry out a review and re-design of the KPN study curriculum that is owned to suit the needs of the industry or as known as “link and match”.